2012
DOI: 10.1038/nphoton.2012.45
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic interferometry

Abstract: nature photonics | VOL 6 | MARCH 2012 | www.nature.com/naturephotonics 139 research highlights and numerically. The nanojets had a waist of 205 nm and a divergence angle of 3.3 º -more than ten times smaller than the Gaussian focus spot. These nanojets could be useful for on-chip applications in biosensing and single-molecule detection. NH optomechanics electrical coupling Phys. Rev. Lett. 107, 273601 (2011)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…In spite of over 100 years of use, interferometric approaches for measurement are still widely used as was seen in gravitational waves being experimentally confirmed through the results obtained from an interferometer [5]. The use of a Michelson interferometer with a plasmonic device has been recently reported by Nithiroth et al [9,10] with the use of other plasmonic interferometers found in recent literature [11][12][13][14][15][16][17]. There are many other interesting applications of plasmonic waves in the literature [18,19] and [20,21], where interesting plasmonic propagation and plasmonic graphene-Au nanostructure research has been reported.…”
Section: Introductionmentioning
confidence: 90%
“…In spite of over 100 years of use, interferometric approaches for measurement are still widely used as was seen in gravitational waves being experimentally confirmed through the results obtained from an interferometer [5]. The use of a Michelson interferometer with a plasmonic device has been recently reported by Nithiroth et al [9,10] with the use of other plasmonic interferometers found in recent literature [11][12][13][14][15][16][17]. There are many other interesting applications of plasmonic waves in the literature [18,19] and [20,21], where interesting plasmonic propagation and plasmonic graphene-Au nanostructure research has been reported.…”
Section: Introductionmentioning
confidence: 90%
“…Generally, the interferometry has also been employed in many areas of applications (Bartoli, ; Dyer, ; Feng et al, ; Gan & Batoli, 2011; Li, Feng, & Pacifici, ; Szuatakowski & Palka, ) such as sensors, signal processing, communication, medicine, drug delivery. To date, the interferences of the small scale and the large system such as the squeezed photon up to the gravity wave were constructed by the interferometer (Coyne, ; Feng et al, ; Graydon, ; Li et al, ; Steinlechner et al, ; Weir, Boyle, Meggit, Palmer, & Grattan, ), where the quantum interferometer has also been reported in both theoretical and experimental works, in which the wave‐particle properties have been formulated, in which their interactions within the interferometer formed and detected. Many works of the interferometers have been employed since the Weiss prototype announced (Shoemaker et al, ), however, there are still some problems to solve, therefore, the searching of the new interferometric systems is continued by the available new materials and detection techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmons are collective and coherent plasma oscillations of free electrons in metallic materials which play a fundamental role in the optical properties of metals [1]. This has stimulated a wide range of theoretical investigations and applications, such as optical metamaterials [2,3], solar cells [4][5][6][7], biochemical sensing [8], and antennas [9,10]. The classical Drude model is the most accepted theoretical framework to model the dielectric permittivity in metallic structures [11][12][13].…”
Section: Introductionmentioning
confidence: 99%